The Extended Enterprise Reference Framework - O'Neill, Henrique; Sackett, Peter (Balanced Automation Systems - Implementing challenges for anthropocentric manufacturing, 1996)
Technologies offer a powerful enabling mechanism for companies to increase their competitive advantage. To exploit its full business performance potential, the application of technology must be aligned with the mission, objectives and goals of the business, and be integrated with the people and the organisational elements. Changing environmental conditions demand the development of new ways to visualise and to design businesses. Reference frameworks facilitate management development of the business vision and enables alignment of vision across the organisation. This article presents a new reference paradigm for the emerging manufacturing industry vision: the Extended Enterprise. The authors detail a prescriptive framework to realise the Extended Enterprise.